A Quantum City Mastering the Generic (Applied Virtuality Book Series, 2015)
We know the specific strengths of various cities, are aware of their ranking, are able to discuss their density and growth. But what do all cities have in common, what do we know about their "lowest common denominator"?The "city as a species", the "primal genetic material of the city": this is the subject of A Quantum City. This colossal work is a love letter to the city and intellectual culture